Formation of Stalin’s сult in Soviet Belarus in 1934–1939 - Huzhalouski , Alexander A. (Journal of the Belarusian State University. History, 2019)
Оn the basis of archival sources, periodicals and contemporary research works, сonsolidation of Stalin’s cult in Soviet Belarus is presented in the article. The few works that appeared during the two waves of de-Stalinization – in the second half of the 1950 – 1960s and in the second half of the 1980 – 1990s – did not reveal the phenomenon of the cult of the leader in Soviet Belarus. They only indicated the contours of this problem, without clarifying its essence, specific forms and consequences. The author gives an opportunity to a reader to examine the period from the 17th Congress of the CPSU(b), when the cult began to actively develop until the 60th anniversary of Stalin, when he reached his zenith. Supplemented by unlimited violence, the cult of Stalin was as effective as the Marxist doctrine to mobilize the society for support of Soviet totalitarian regime. The cult origin was rooted in a traditional, archaic society. It had irrational nature, what reflected the entire Soviet political culture. The main tool for leader’s cult construction was the party bureaucracy, true ruling class of Soviet society. The cult was introduced through the propaganda machine and was essentially a state religion with its own sacred texts, dogma, rituals, rites, holidays, and shrines. Under the direction and control of the party leadership, the image of a charismatic leader – the father, the teacher, the creator of a brighter future was purposefully formed during the second half of the 1930s with the help of media, literature, art, and educational institutions.
Keywords: cult of Stalin; Soviet Belarus; party bureaucracy; totalitarian regime; mass media; literature; art; anniversary; state religion